Incidence of Delivery Complications Based on Age and Parity: Kejadian Komplikasi Persalinan Berdasarkan Usia dan Paritas - Maulida Zahro; Siti Cholifah (Academia Open, 2023)
General Background complications during delivery can significantly affect maternal and neonatal outcomes, necessitating a deeper understanding of associated risk factors. Specific Background this study examines the relationship between maternal age, parity, and the incidence of delivery complications in a local healthcare setting. Knowledge Gap limited research has focused on the impact of maternal characteristics, such as age and parity, on the prevalence of delivery complications within this population. Aims the research aims to analyze the incidence of complications among mothers based on their age and parity status using descriptive survey design and secondary data. Results the findings indicate that a majority of mothers were at risk due to age, with 65% being unemployed and 60% experiencing irregular antenatal care (ANC). Furthermore, 65% of the mothers were classified as multigravida, and 65% faced complications during delivery. The incidence of complications was higher among those at risk (75%) compared to those not at risk (50%). Additionally, multigravida mothers experienced a higher complication rate (84.6%) than primigravida (20.0%) and grandemultigravida (77.8%). Novelty this study highlights the significant prevalence of delivery complications linked to maternal age and parity in a specific healthcare setting. Implications these findings underscore the importance of targeted healthcare interventions and improved prenatal care to mitigate risks associated with delivery complications. Highlights: Majority of mothers at risk due to age and parity. High incidence of delivery complications among multigravida. Irregular antenatal care linked to increased complications. Keywords: Complications, Maternal Age, Parity, Antenatal Care, Multigravida